PENGARUH BRAND FAMILIARITY TERHADAP BRAND CREDIBILITY - Seri Marianti; Tito Adi Dharma; Lingga Yuliana (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to analyze the influence of Brand Familiarity on Brand Credibility with a case study of skincare products with the Scarlett brand. No previous research has been found related to research variables that examine the correlation between brand familiarity to brand credibility with Scarlett's brand case study. Descriptive quantitative became the method in this study. Involving 75 respondents domiciled in Baturaja City who are users of the Scarlett brand, both men and women. Data analysis techniques using Partial Least Square (PLS). Using primary data disseminated through Google Forms with a data collection period of August 2023. The results showed that there was an influence between brand familiarity and brand credibility. The presence of scarlett skincare as a local brand can be considered for the reliability of the brand so that it can be the choice of the community instead of using imported products. This will have an impact on increasing scarlett products which will help the economy of resellers and skincare owners